The algorithm of dental care for pregnant women (Эндодонтия Today)
Pregnant patients at the dental reception represent a special risk group due to some specific physiological rearrangements that occur in a woman’s body. This is the time of an active growth of dental diseases and exacerbation of previously existing chronic infections, both somatic and cavitary. Taking into account the duration of gestation, critical periods and comorbidity, determined was an algorithm of providing safe dental care including development of methods for correction of mental and emotional state of a pregnant woman as well as a safe local anaesthesia.